Efektifitas Rebusan Daun Sirih Terhadap Penyembuhan Luka Perineum di Klinik PPK 1 Yonkes 1 Kostrad Bogor Jawa Barat Tahun 2023 - Elfira Rusana; Lasria Simamora; Henny Rista; Lidia Sinuhaji (Pusat Riset dan Inovasi Nasional, 2024)
Background: Based on data from the World Health Organization in 2015, the number of maternal deaths is around 2.7 million cases, perineal rupture in delivering mothers, this figure is estimated to reach 6.3 million by the year 2050, some of which are caused by perineal wounds. According to the Demographic and Health Survey data in Indonesia in 2017, the maternal mortality rate is 305/100,000 live births caused by infections, including those in perineal wounds. The maternal mortality rate in various provinces in Indonesia has decreased from 4,226 to 4,221. In 2019, the highest maternal mortality rate was attributed to hemorrhage (30.3%) and postpartum infection (5%) (Indonesian Health Profile, 2019). One of the indicators to reduce maternal mortality during childbirth is preventive efforts undertaken during the postpartum period. These efforts include both medical and traditional treatments. Traditional wound treatment using natural ingredients such as red betel leaf, turmeric tamarind concoction, binahong, etc., has been proven to have chemical components that can kill Staphylococcus aureus bacteria and Candida Albicans fungus, thereby accelerating the healing process (Sari, 2017). Red Betel Leaf (Piper Crocatum) is a very popular traditional remedy and is most commonly found in Indonesia. This study aims to analyze the Effectiveness of Red Betel Leaf Decoction on Healing Perineal Wounds of Degree II at the PPK 1 Clinic, 1st Yonkes 1 Kostrad Bogor, West Java in 2023. Method: This is a quantitative study using quasi-experimental methods, which includes a control group. The research design used is a posttest-only control group design. The population of this study is all postpartum mothers at the PPK 1 Clinic, 1st Yonkes 1 Kostrad Bogor, West Java, who experienced perineal tears from March to June 2023, with a sample size of 30 postpartum mothers, divided into 15 experimental groups and 15 control groups. In this study, sampling was done using a non-probability sampling approach, specifically purposive sampling. Results: The statistical test results yielded a p-value of 0.024 (p<0.05), indicating a significant difference between the average healing time of perineal wounds in the intervention group and the control group. Conclusion: There is a significant difference between the average healing time of perineal wounds in the intervention group and the control group. It is hoped that this can become an alternative choice for non-pharmacological treatment and serve as an evaluation material regarding the influence of red betel leaf decoction on perineal wound healing, thus it is recommended for midwives to enhance education to postpartum mothers on the use of red betel leaf as a means of treating perineal wounds.